Use of Information and Communication Technology for Effective Teaching of Physical Education in Universal Basic Education: The Nigerian Experience - Nwabuwe Sunday Nathaniel; Nwabuwe Henrietta Ifeanyichukwu; Emuobonuvie Erhinyoja Andy (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. Technology has influenced teaching, yet we know little about physical educators’ predispositions and use in Universal Basic Education (UBE). One of the goals for integrating information and communication technology (ICT) in teaching physical education is to enhance teaching and learning practices, thereby improving the quality of education at this level. However, in most developing countries like Nigeria, the potential of ICT to support pedagogy is yet to be fully realized. Up until now, most of the attention, both in policy and research, has been on how the lack of infrastructure and access to technology affect the use of ICT in Universal Basic Education (UBE). So this paper x-rays: how ICT in physical education is designed as a tool for increasing instructional effectiveness in UBE, the impact of ICT use on classroom teaching and learning in UBE, and the path towards effective implementation of ICT in Universal Basic Education. Recommendations were made to effect the appropriate use of information and communication technology in teaching physical education in the universal basic education programme. Keywords: ICT, Teaching, Physical Education, Universal Basic Education